Perbandingan Cara Pengolahan Kakao Lindak (Bulk Cocoa) pada Perkebunan Besar Negara dan Perkebunan Swasta di Glenmore, Kabupaten Banyuwangi, Jawa Timur - Hatiningsih, Sayi; Mayun Permana, Dewa Gde; Suwasono, Sony (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 9 No 2 (2020): Jurnal ITEPA, 2020)
The excellent quality of the cocoa beans is closely related to the processing of cocoa beans. This study aimed to compare the processing of bulk cocoa on the government estate and the private estate on Glenmore, Banyuwangi, East Java. The method use observation, interviews, and literature study to record relevant information, then analyzed with descriptive and qualitative analysis. The result showed that the government estate and the private estate on Glenmore, Banyuwangi, East Java did pay attention to the quality of cocoa beans because of the processing methods of cocoa beans of that two cocoa estates had been good, especially with the fermentation of cocoa beans. The processing of cocoa beans on the government estate on Glenmore, Banyuwangi, East Java comprises receiving raw materials, fermentation, washing or rinsing, drying, tempering, sorting, packaging, and storing. The processing of cocoa beans on the private estate on Glenmore, Banyuwangi, East Java comprises receiving raw materials, pressing, fermentation, drying, sorting, packaging, and storing. Keywords: processing of cocoa beans, Glenmore estate, fermentation.